Analysis of the rate of socio-economic changes in rural areas between 2010 and 2020. Polish case - Bąk, Iwona; Wolska, Grażyna; Wawrzyniak, Katarzyna; Oesterreich, Maciej (Bulletin of Geography. Socio-economic Series, 2022)
The article presents the results of research on the transformation process in the Polish country-side between 2010 and 2020, taking into account those rural communes where the State-Owned Farms (PGR) were located. The study aimed to identify the spatial diversity of post-PGR communes on the grounds of socio-economic situation and to assess the rate of change in this situation in the surveyed communes over 11 years, as well as to answer the question how the socio-economic situation was influenced by the location of a given commune relative to province capitals. In the analyses, selected methods of descriptive statistics and multidimensional comparative analysis were applied. The results confirmed that in many post-PGR communes, also these days, we can observe financial problems, and that people experience significant difficulties with entering the labour market. The research also showed that in most cases communes located close to these cities were characterized by a better socio-economic situation than the communes located further away.